Reverse logistics system design for the waste of electrical and electronic equipment (WEEE) in Turkey - KILIÇ, HÜSEYİN SELÇUK; AYHAN, MUSTAFA BATUHAN (ELSEVIER, 2015)
Depending on the high consumption in the world, the amount of waste increases. One of the critical waste types to be handled is the electrical and electronic waste (WEEE). The recovery of WEEE is very important both from environmental and economic aspects and has become mandatory in most of the countries in the world. Reverse logistics which is mainly the backward flows of used products from consumers to producers is an important stage while constructing a recovery system. The network structure of reverse logistics system plays an important role in the total cost of the recovery system. These structures mainly include the locations of facilities and the flows between the related points. With this study, a reverse logistics system is designed for WEEE in Turkey which is one of the fast developing countries in the world. Ten scenarios are taken into account regarding different collection rates via a mixed integer linear programming model. Different types of storage sites and recycling facilities are considered within the model differing from the existing studies. The optimum locations of storage sites and recycling facilities are obtained for each scenario satisfying the minimum recycling rates stated by the European Union directive for each product category. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: WEEE; Network design; Mixed integer linear programming; Recycling rate; RECOVERY NETWORK; LOCATION; MODEL; COLLECTION; APPLIANCES